Modelo de gestión turístico sostenible para la planificación estratégica en el cantón Pedernales. - Dueñas Navarrete, Juan Francisco (2015)
The research developed a Sustainable Tourism Management Model for strategic planning in Pedernales province of Manabi. A selection of territory was done to identify entities and collaborators, an analysis of tourism to identify supply and demand, with the result that most cities are in need of improving infrastructure and tourism promotion. The participatory aspect link communities to tourism, determining that itself is interested in developing new tourism alternatives, the selection of indicators worth to be aware of important issues for management; a comprehensive diagnosis matrix was used to structure Weaknesses, Threats, Strengths and Opportunities, knowing the main potentialities that Pedernales has and its shortcomings, and develop relevant strategies and Sustainable Tourism Management Model for strategic planning structures, stages and courses of action, which is simplified in a process diagram. It is concluded that the model of sustainable tourism management will assist the authorities and stakeholders involved in tourism can planning various areas and promote sustainable tourism actions, in addition to presenting interesting because it includes aspects that can be converted in support for further research in Pedernales.